PENGARUH DISIPLIN KERJA, PENGEMBANGAN KARIR DAN KOMPENSASI TERHADAP KINERJA KARYAWAN PADA HOTEL DIBAWAH NAUNGAN MANAJEMEN WARINGIN HOSPITALITY DI KOTA JEMBER - Diana Nuril Kamilah; Agus Priyono; Chairul Saleh; Ema Desia Prajitiasari; Ika Barokah Suryaningsih; Yustri Baihaqi (VALUE: Journal of Business Studies, 2023)
Human resources are vital things that become main movers to achieve the goals of an organization. Employee performance is very influential on the success of a company. The better the performance of employees in a company, the easier it will be for the company's process to achieve its goals. In the midst of the property business rampant, including hotels that went out of business during the pandemic due to the declining occupancy rate, Hotel 88 Jember and Luminor Hotel Jember managed to survive and climb back up again because they were able to maintain the performance of their employees. This is an important problem to overcome decreased occupancy rate that may occur in the future of hospitality business in Indonesia. This study aims to examine and analyze the effect of work discipline, career development and compensation on employee performance at hotels under the management of Waringin Hospitality in Jember City. The object of this research is the population of employees at hotels under the auspices of Waringin Hospitality Management in Jember City, namely Hotel 88 Jember and Luminor Hotel Jember with a total population of 46 employees. The research data was collected by distributing questionnaires directly. The data analysis method in this study used multiple linear regression analysis. This study shows that the variables of work discipline, career development and compensation have an effect on employee performance at hotels under the auspices of Waringin Hospitality Management in Jember.